Development of a Fresh Approach to Use Cooperative Diversity for Efficient & Effective Communication in Modern Wireless Systems - Srivastava, Alok; Rajeev Ratan, Dr. (International Journal of Engineering and Technology, 2018)
Cooperative communication system for wireless mobile system is the most challenging and powerful technology for implementation in the mobile and wireless communication domain. Though, various protocols have been suggested for cooperative communication, but none of them is feasible in implementation because of attenuation, noise and cost. In this paper, all the systems used are incorporated by traditional mobile system with minimum changes, so that cost can be minimized. In the proposed approach we use a multiple input multiple output technique at receiver end to improve signal strength. Random data packets have been generated which have been modulated using QPSK technique and then passed through all types of attenuations and noises. The received packets were then analyzed in terms of signal to noise ratio (SNR) and symbol error rate (SER) [1]. It has been found that more than 5dB improvement has been achieved in comparison to traditional mobile system. Â Â